Character Development and Deviant Behavior: A Systematic Review of Theft Among Students in Educational Environments - Priyanto, Firman; Mustofa, Triono Ali; Jinan, Mutohharun (Universitas Muhammadiyah Surakarta, 2025)
In schools and colleges theft of students' property is a chronic problem that influences the formation of students' character and social activity. This is not only to the detriment of the quality of education, but it also undermines confidence between teachers and students and parents. So the purpose of this study is to rise over what induced stealing behavior, developing character students stolen acts and what institutions could do not be a person who likes to steal. The research employ method is a systematic literature review with qualitative approach reviewing and analyzing on character building, criminal behavior, and student theft. Searches for literature were made on international databases using the key words